Fluidized-Bed Granulation of Probiotics-Encapsulated Spray-Dried Skim Milk Powder: Effects of a Fluidizing Aid, Moisture-Activation and Dehydration - Lim, Dong-Hyun; Letona, Andres; Lee, Minjeong; Lim, Dayoung; Han, Nam-Soo; Chung, Donghwa (Foods, 2021)
A probiotic powder of poor flowability with high dust content, prepared by spray drying reconstituted skim milk fermented with Lactobacillus rhamnosus GG (LGG), was granulated by fluidized-bed granulation (FBG). The effects of the addition of skim milk powder (SMP) as a fluidizing aid, and of simple moisture-activation with or without dehydration, were investigated with respect to the performance of the FBG process. A fine, poorly fluidizable LGG powder (Geldart Group C) could be fluidized and granulated, with a 4- to 5-fold increase in particle size (d4,3 = 96–141 μm), by mixing with SMP (30–50%), which has larger, fluidizable particles belonging to Geldart Group A. Moisture-activation after the mixing, followed by fluidized-bed dehydration with hot air to remove excess moisture, further improved the FBG; the yield of the granules increased from 42% to 61% and the particle size distribution became much narrower, although the average particle size remained almost the same (d4,3 = 142 μm). These granules showed a popcorn-type structure in scanning electron microscopy images and encapsulated a sufficient level of viable LGG cells (1.6 × 108 CFU g−1). These granules also exhibited much better flowability and dispersibility than the spray-dried LGG powder.